PENGARUH PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XII MIPA SMA NEGERI 8 PADANG - Lubis, Wanda Efriyani (Jurnal Edukasi dan Penelitian Matematika, 2023)
Problem solving skills in mathematics are crucial. Based on the initial test results of class XII MIPA at SMA Negeri 8 Padang, they are still unable to solve problems correctly according to the indicators. In order to overcome this, the Contextual Teaching and Learning (CTL) model was implemented. This study tested whether those taught with the CTL approach can solve math problems better than those taught conventionally. This research used Quasy Experimental Design with Static Group Design. The research population was class XII MIPA SMA Negeri 8 Padang, with samples of classes 1 and 4. The instrument used was a test in the form of essay questions. The t-test data analysis resulted in a P-value = 0.000. Therefore, H0 is rejected. Thus, CTL in class XII MIPA SMA Negeri 8 Padang solves math problems better than ordinary learning.Keywords– Mathematical Problem Solving Ability, Contextual Teaching and Learning, Mathematics